2002
DOI: 10.1200/jco.2002.06.119
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab in Previously Treated Chronic Lymphocytic Leukemia Patients Who Also Had Received Fludarabine

Abstract: Alemtuzumab has significant activity in poor-prognosis, fludarabine-treated CLL patients. However, because of a relatively high incidence of opportunistic infections accompanying profound lymphopenia, future protocols should include mandatory prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
148
3
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(176 citation statements)
references
References 9 publications
14
148
3
11
Order By: Relevance
“…However, infection rates correlated with response, with only two of eight responders developing infections, compared with eight of 16 nonresponders. 21 Similar infection rates were noted in a study by Keating et al 5,22 Perkins et al 23 retrospectively reviewed the frequency and severity of serious infections in fludarabine-refractory CLL. Of 27 patients with fludarabine-refractory disease who were receiving no therapy, 24 (89%) developed serious infections, which occurred at a median of 4 months after the onset of fludarabine refractoriness.…”
Section: Management Of Infectious Complicationssupporting
confidence: 55%
“…However, infection rates correlated with response, with only two of eight responders developing infections, compared with eight of 16 nonresponders. 21 Similar infection rates were noted in a study by Keating et al 5,22 Perkins et al 23 retrospectively reviewed the frequency and severity of serious infections in fludarabine-refractory CLL. Of 27 patients with fludarabine-refractory disease who were receiving no therapy, 24 (89%) developed serious infections, which occurred at a median of 4 months after the onset of fludarabine refractoriness.…”
Section: Management Of Infectious Complicationssupporting
confidence: 55%
“…In the pivotal study of alemtuzumab in patients with relapsed/refractory disease, CD19 + /CD5 + B cells and CD3 + /CD4 + and CD3 + /CD8 + T cells were significantly depressed after 4 weeks of treatment [30]; these findings were confirmed by another study that also noted a decrease in CD16 + natural killer (NK) cells [49]. The T-cell population gradually recovered to baseline levels by 36 weeks after therapy initiation [30].…”
Section: Effect Of Alemtuzumab On Immune Cellsmentioning
confidence: 85%
“…In another study in patients with relapsed or fludarabine-refractory CLL, infections were reported in 42% of patients, predominantly in the non-responder group. Seven of eight non-responders developed major infections during treatment and within 35 days following treatment completion, and two of them died from infections [49]. Similarly, in the pivotal study of 93 relapsed/refractory CLL patients, 25 patients (27%) experienced grade 3/4 infectious events (27%), which occurred more frequently in non-responders than in responders (36% versus 9.7%) [30].…”
Section: Infectious Events Associated With Alemtuzumab Therapymentioning
confidence: 88%
See 1 more Smart Citation
“…Despite that infection, prophylaxis was put in force beginning on day 8 and continuing for a minimum of 2 months after treatment, and grade 3 or 4 infections were reported in 27% of the heavily pre-treated patients, including pneumocystis and aspergillus pneumonia, systemic candidiasis, cryptococccal pneumonia and listeria meningitis leading to death in 11 patients. Based on these data and other trials [36,37], alemtuzumab received the orphan status and was approved by the FDA for the treatment of CLL refractory to fludarabine in 2001.…”
Section: Alemtuzumab (Campath ® )mentioning
confidence: 99%